1995
DOI: 10.1002/bjs.1800821035
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in surgery for local recurrence of rectal cancer

Abstract: Fifty-five patients had resection of locally recurrent rectal cancer. Fourteen patients (25 per cent) had distant metastases, which were resected concurrently in six (11 per cent). Thirty-three patients (60 per cent) had preoperative (one patient) or postoperative (32) external beam radiotherapy (45-60 Gy). The 5-year survival rate was 18 per cent with a median survival of 24 months. The median symptom-free interval was 24 months. At a median follow-up of 28 months 53 per cent of patients had a second local re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 24 publications
2
44
1
Order By: Relevance
“…The St. Mark’s group found four factors associated with longer survival: radical nature of the operation, absence of severe symptoms, a recurrent tumor <5 cm in diameter, and CEA level <5 ng/ml; however, tumor diameter was the only independent prognostic factor [23]. Wanebo et al [15]reported that patients with previous APR and CEA levels >10 ng/ml had a worse 5-year survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The St. Mark’s group found four factors associated with longer survival: radical nature of the operation, absence of severe symptoms, a recurrent tumor <5 cm in diameter, and CEA level <5 ng/ml; however, tumor diameter was the only independent prognostic factor [23]. Wanebo et al [15]reported that patients with previous APR and CEA levels >10 ng/ml had a worse 5-year survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report the role of early detection of local recurrence in resectability and prognosis after resection [15, 23, 24, 25]. The St. Mark’s group found four factors associated with longer survival: radical nature of the operation, absence of severe symptoms, a recurrent tumor <5 cm in diameter, and CEA level <5 ng/ml; however, tumor diameter was the only independent prognostic factor [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these invasive procedures should only be considered in carefully selected patients. Although significant prognostic factors influencing the outcome of surgery for local recurrence have been identified, such as postoperative tumor marker levels and pathological curativity of surgical margins [17, 18], recognizable factors after surgery are not useful in determining the indications for surgery. As a result, factors which can be found preoperatively must be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy dose was specified in 28 studies. [3][4][5][6][7][8][9]11,18,19,28,29,30,[33][34][35][36][37]41,44,46,47,[50][51][52][53]56,57 Without prior EBRT, the total dose was 40-60 Gy in most studies, with an overall range of 15-80 Gy. Conventional fractionation (1.8-2.0 Gy per fraction) was uniformly applied in 13 studies, 3,6,7,9,11,18,19,28,30,36,46,50,52 and selective use of a hypofractionated schedule (fractions of 5 Gy) was described in 2 studies.…”
Section: Perioperative Treatment For Local Recurrencementioning
confidence: 99%